Metode Pembelajaran Bahasa Arab untuk Anak Usia Dini Menggunakan Aplikasi Digital - Agustini; Qoriatunnisak (Journal of Innovative and Creativity, 2025)
The development of digital technology has opened up opportunities in the world of education, including in learning Arabic for early childhood. Digital applications offer interactive and interesting media, so it can increase children's interest and motivation in learning Arabic. This study aims to examine the methods of learning Arabic for early childhood using digital applications, and evaluate its effectiveness in improving Arabic language skills in early childhood. This study uses field research methods with a descriptive qualitative approach. The research subjects were early childhood children in TK AL-MUSTAQBAL Malang. Data collected from observations, interviews, participation, and documentation. The results showed that the method of learning Arabic for early childhood using digital applications proved effective in improving vocabulary, understanding grammar, and speaking skills in Arabic. These results are based on the facts on the ground that most of the students of TK AL-MUSTAQBAL have been able to use Arabic for beginners.